2013
DOI: 10.1080/02786826.2013.857758
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Sources of the Organic Particle Emissions from Aircraft Engines

Abstract: We report a positive matrix factorization (PMF) analysis of organic particulate material (PM) emissions of aircraft engine exhaust that includes data from five different aircraft engines and two different fuels (petroleum jet fuel and a Fischer-Tropsch fuel) collected over three field missions. PMF of aerosol mass spectrometer (AMS) data was used to identify six distinct factors: two lubrication oil factors, two aliphatic factors, an aromatic factor, and a siloxane factor. Of these, the lubrication oil factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 65 publications
1
28
1
Order By: Relevance
“…Zhang et al, 2007), or during source studies (e.g. Elsasser et al, 2013;Timko et al, 2014;Corbin et al, 2015a).…”
Section: Influence On Positive Matrix Factorization Resultsmentioning
confidence: 99%
“…Zhang et al, 2007), or during source studies (e.g. Elsasser et al, 2013;Timko et al, 2014;Corbin et al, 2015a).…”
Section: Influence On Positive Matrix Factorization Resultsmentioning
confidence: 99%
“…Common practices were used to postcorrect the air beam (AB) to account for natural drift in the instrument sensitivity (Allan et al 2003b). As recommended by Timko et al (2009Timko et al ( , 2014, we have also removed signal contributions related to the contamination artifacts that arise from the fragmentation of aerosolized polydimethylsiloxane (SiO(CH 3 ) 2 ), found in conductive silicone tubing.…”
Section: Hr-ams Operationmentioning
confidence: 99%
“…Fuel aromatic content varied between 14.5% and 22.7% and sulfur content between 200-700 ppm depending upon the engine/aircraft particular test. Further details may be found in references [27,28]. For this same range the fuel hydrogen fraction varied between 0.137 and 0.147.…”
Section: Methodsmentioning
confidence: 98%
“…Timko et al reported significant organic content in PM sampled from idle conditions [26]. Recently both Timko et al [27] and Yu et al [9] found lubrication oil contribution to volatile PM. All such measurements were performed using the Aerodyne aerosol mass spectrometer.…”
Section: Accepted Manuscriptmentioning
confidence: 94%
See 1 more Smart Citation